Arquitetura da informação para biblioteca digital colaborativa: uma proposta de um sistema de interação - Inafuko, Laura Akie Saito [UNESP] (2013)
Digital libraries are informational environments that allow the storage, representation, organization, preservation, access, retrieval and (re)use of information. The informational structures of digital libraries must adapt to the needs and capabilities and conduct the informational behavior of the user, so he can build his own knowledge. Thus, digital libraries can be built on the principles of information architecture to ensure that the user of an environment has access to information more quickly, easily and intuitively. With the development of collaborative web appears the concept of “library 2.0” which brought to traditional libraries the dynamism of collaborative tools and invite users to participate and interact with the environment in the digital library. In this dissertation it is considered that digital libraries must adapt to the collaborative paradigm, due to the emergence of new digital services and the transformation of the consuming user into a content producing user. This way, one of the problems this research has found is the absence of a model of information architecture for collaborative digital libraries, specifically the elements that may guide the interaction and collaboration within the environment. In such context, our objective is to propose a system of interaction within Information Architecture Systems already proposed by Morville and Rosenfeld (2006) for the environment of Collaborative Digital Libraries, from architectural elements of information selected from literature and from the survey of the usage of web tools for collaborative digital libraries